In Tiflis (Georgia). Dedication from Central Committee of the Trade Union of Georgian State Railway Personnel to Kautsky - Grinevič', V.K., (1920)
In Tiflis (Georgia). Dedication from Central Committee of the Trade Union of Georgian State Railway Personnel to Kautsky.